solve 44=14-2a

Guide :

solve 44=14-2a

how to solve this equation

Research, Knowledge and Information :


44=14-2a - solution


Simple and best practice solution for 44=14-2a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t ...
Read More At : www.geteasysolution.com...

Solve 44 = 14 - 2a? - Weknowtheanswer


Solve 44 = 14 - 2a? Find answers now! No. 1 Questions & Answers Place. More questions about Science & Mathematics, Mathematics
Read More At : www.weknowtheanswer.com...

solve 44= 14-2a i hate these kind of problems they screw wit ...


algebra solve 44= 14-2a i hate these kind of problems they screw wit ur head that's what i think anways i just need help quiz comparing fractions
Read More At : www.jiskha.com...

Check my answer. Solve 44 = 14 - 2a. My answer: ... - OpenStudy


Check my answer. Solve 44 = 14 - 2a. My answer: first we subtract 14 from both sides, 44 - 14 = 14 - 14 - 2a = 30 = - 2a, now we divide both sides b...
Read More At : openstudy.com...

Solve 44 = 14 - 2a? - Drumtom


Find right answers right now! Solve 44 = 14 - 2a? More questions about Science & Mathematics
Read More At : www.drumtom.com...

44 = 14 − 2a. y – 5 = –8 –7b = 21 −5 ... - OpenStudy


44 = 14 − 2a. y – 5 = –8 –7b = 21 −5 = c / 7 these are all the ones i need help with 44=14-2a Simple and best practice solution fo...
Read More At : openstudy.com...

Suggested Questions And Answer :


how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero an
Read More: ...

How do I solve y=-x-4

How do I solve y=-x-4 I need to be able to plot these points on a graph but i don't know how to solve the problem.   make an x & y axis. ( like a cross one line goes vertical an the other horizontal) put equal dimention for x & y line From center line moving
Read More: ...

x - z = -3, y + z = 9, -2x + 3y +5z = 33

Problem: x - z = -3, y + z = 9, -2x + 3y +5z = 33 1) x - z = -3 2) y + z = 9 3) -2x + 3y + 5z = 33 Add equation 2 to equation 1.      x     - z = -3 +(    y + z =  9) ------------------   x + y     = 6 4)
Read More: ...

(13-3)x5=50

Simplifying x + 2 = 3x + -1x2 + 5 Reorder the terms: 2 + x = 3x + -1x2 + 5 Reorder the terms: 2 + x = 5 + 3x + -1x2 Solving 2 + x = 5 + 3x + -1x2 Solving for variable 'x'. Reorder the terms: 2 + -5 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Combine like terms: 2 + -5 = -3 -3 + x + -3x + x2
Read More: ...

(8x)[(2x)^-2=8

Simplifying 8x = 2x2 + 8 Reorder the terms: 8x = 8 + 2x2 Solving 8x = 8 + 2x2 Solving for variable 'x'. Reorder the terms: -8 + 8x + -2x2 = 8 + 2x2 + -8 + -2x2 Reorder the terms: -8 + 8x + -2x2 = 8 + -8 + 2x2 + -2x2 Combine like terms: 8 + -8 = 0 -8 + 8x + -2x2 = 0 + 2x2 + -2x2 -8 + 8x + -2x2
Read More: ...

Whats 3x-2 over 9 equals 25 over 3x-2?

I will give you an example for this question. This might be able to help you. Simplifying 3x2 + 25x = 18 Reorder the terms: 25x + 3x2 = 18 Solving 25x + 3x2 = 18 Solving for variable 'x'. Reorder the terms: -18 + 25x + 3x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -18 + 25x + 3x2 = 0 Fac
Read More: ...

3x + 6y – 6z = 9 2x – 5y + 4z = 6 -x +16y + 14z = -3 what is the answer

3x + 6y – 6z = 9 2x – 5y + 4z = 6 -x +16y + 14z = -3 what is the answer how do you solve it and what are the answers ? 1)  3x + 6y – 6z = 9 2)  2x – 5y + 4z = 6 3)  -x +16y + 14z = -3 The first objective is to eliminate z so we can solve for x and y. It's a multi-step proces
Read More: ...

what is general solution for dw/dt = 7w+6y-10z

what is general solution for dw/dt = 7w+6y-10z dx/dt= 3w + x +3y-5z dy/dt= 5w+2x+11y-14z dz/dt=5w+2x+8y-11z Represent the coupled differential equations in matrix form. X = Av Where X is the column vector [w’ x’ y’ z’] and x’ = dx/dt, etc. And A is the component mat
Read More: ...

solve for x: 3x^2-5x+2=0

Problem: solve for x: 3x^2-5x+2=0 solve for x: 3x^2-5x+2=0 (3x - 2)(x - 1) = 0    set each factor to zero and solve for x (3x - 2) = 0 3x = 2 x = 2/3 (x - 1) = 0 x = 1 Check. 3x^2 - 5x + 2 = 0 3(2/3)^2 - 5(2/3) + 2 = 0 3(4/9) - 10/3 + 2 = 0 4/3 - 10/3 + 2 = 0 -6
Read More: ...

solve for x when (.182+x)/(.106-2x)=3.24

solve for x when (.182+x)/(.106-2x)=3.24 Im trying to solve for x its for a chemistry equation but i need to solve for x using the quadratic equation and i dont know which equals a b and c to find x. ************************** You can't solve this with the quadratic formula, because there is no x^2
Read More: ...

Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question
  • Start your question with What, Why, How, When, etc. and end with a "?"
  • Be clear and specific
  • Use proper spelling and grammar
all rights reserved to the respective owners || www.painphr.com || Terms of Use || Contact || Privacy Policy
Load time: 0.0977 seconds